Constructing a Private Cloud Computing Platform Based on OpenStack - Xiaoning Li; Lei Li; Lianwen Jin; Desheng Li (Dianxin kexue)
Cloud computing is a very popular research direction in the IT field in recent years, and private cloud is very important in cloud computing because itˊs safety, controllability and effective use of IT equipment resources. This paper introduces the architecture of an open source cloud computing platform OpenStack and the relationship between five functional modules in OpenStack. This paper also highlights a method of building private cloud based on OpenStack. In addition, this paper shares the problems met in building the private cloud platform and the solutions of solving the problems. In the end, this paper analyzes the security and flexible computing resource allocation capabilities of the private cloud platform.